Clinical Efficiency of Low-Level Diode Laser in Reducing Dentin Hypersensitivity - Clavijo, E. M. A.; Clavijo, V. R. G. [UNESP]; Bandeca, Matheus Coelho [UNESP]; Nadalin, M. R.; Andrade, M. F. [UNESP]; Saad, José Roberto Cury [UNESP]; Pelegrine, A. A. (Maik Nauka/interperiodica/springer, 2009)
Dentin hipersensitivity (DH) is a relatively common clinical condition, especially in periodontal patients after treatment. In this study it was evaluated 28 teeth who presented dentin hypersensitivity. The teeth were subjected to clinical and radiographic exams and were divided into groups following the treatment and the time of examination after application proposed: GI: PO 3% (Potassium Oxalate-group control)/Baseline; GII: PO 3%/3 days after first session; GIII: PO 3%/6 days; GIV: PO 3%/30 days; GV: PO 3%/60 days; GVI: PO 3%/90 days; GVII: Laser (Low-level diode laser with 110 mW/cm(2))/Baseline; GVIII: Laser/7 days after first session; GIX: Laser/14 days; GX: Laser/30 days; GXI: Laser/60 days; and GXII: Laser/90 days. The groups I-VI, the teeth were subjected to 3 applications (GI-GIII) of desensitizing agent at regular intervals of seven days. The Groups VII-XI, each tooth was subjected to three applications (GVII GIX) in three different points (mesial, meddle and distal surfaces) with an interval of 72 h. The time of application in each point was of 33 s and the patients from both groups were followed up to 90 days. The nonparametric test Friedman (alpha = 0.05) was applied and the test of Mann Whitney (alpha = 0.05) was used to compare the time of examination between groups. The application of Laser was effective 6 days after first session and to PO was 30 days. It was observed that both treatments were effective for the reduction of dentin hypersensitivity, however the laser presented better effectiveness.